Enhancing vaccine acceptance, hygiene, and trust among community health workers through a microbe literacy intervention: a cluster randomized controlled trial in Sargodha District, Pakistan - Muhammad Tariq; Aamer Ikram; Aslam Asad; Kashif Shahzad Virk; Tehreem Baig; Usman Ali Khan (Journal of Social & Health Sciences, 2027)
A limited understanding of how microbes are transmitted contributes to weak hygiene practices, low immunization uptake, and mistrust of frontline health services in many low-resource settings. This study evaluated whether a microscope-based “germ-watching” community education program (the Microbe Literacy Initiative, MLI), delivered by lady health workers (LHWs), improves hygiene practices, vaccination attitudes and intentions, routine immunization, and trust in LHWs among mothers and female caregivers of children aged three years and under. A two-arm, parallel-group cluster randomized controlled trial was conducted across twelve Union Council (UC) clusters of Sargodha District, Punjab, Pakistan, between 1 May and 31 August 2024, with clusters allocated 1:1 to the intervention or to routine services (six clusters and approximately 600 households per arm; approximately 1,200 households in total). Trained LHWs used portable microscopes to show mothers the microorganisms in their own household samples during a single 120-minute workshop. Hygiene practices, vaccination attitudes and intentions, and trust in LHWs were measured by structured, interviewer-administered surveys at baseline and endline; routine immunization was assessed both from facility-recorded OPV3 coverage and by self-reported completion of the age-appropriate schedule. Because randomization was at the cluster level, effects were estimated at the cluster level using a difference-in-differences comparison of the six intervention and six control clusters, with 95% confidence intervals (CIs); intracluster correlation coefficients (ICCs) were estimated from the baseline data. After accounting for clustering, the intervention was associated with significant improvements in hygiene and immunization: self-reported handwashing increased more in the intervention arm than in the control arm (child handwashing difference-in-differences +46.8 percentage points [pp], 95% CI 8.4 to 85.3, p = 0.025; maternal handwashing +45.0 pp, 95% CI 7.9 to 82.1, p = 0.025), as did self-reported completion of the childhood immunization schedule (+56.3 pp, 95% CI 16.2 to 96.5, p = 0.012); facility-recorded third-dose oral polio vaccine (OPV3) coverage was greater in intervention clusters (98.5% vs 81.8%). Improvements in trust in LHWs (+14.2 pp, 95% CI −23.7 to 52.0), perceived vaccine safety (+15.8 pp), intention to vaccinate (+14.8 pp), and willingness to recommend vaccination (+34.0 pp) were greater in the intervention arm but did not reach statistical significance once clustering was taken into account, reflecting the limited power of six clusters per arm. Several intervention-arm endline values reached 100%, indicating probable ceiling and measurement-reactivity effects; thus, the findings should be regarded as preliminary. A single, low-cost, microscope-based workshop delivered by LHWs was associated with meaningful gains in household hygiene and childhood immunization; effects on vaccine-related attitudes were suggestive but not statistically robust in this small number of clusters and warrant confirmation in a larger, adequately powered trial. The trial was reported following the CONSORT extension for cluster trials and is registered with ClinicalTrials.gov (NCT07771738).